Penerapan Perspektif Generasi dalam Evaluasi Program Pembangunan: Studi Kasus Desa Perpat Kabupaten Belitung - Sutopo, Oki Rahadianto (JURNAL SOSIOLOGI, 2015)
This article aims to apply the generation perspective as a tool to evaluate program of agropolitant village in Perpat, Belitung. Using qualitative methods especially through application of observation and in-depth interview techniques, this evaluation study finds that the change of generation in a local scope and low participations among young people become important factors that resulted in the lack of sustainability of agropolitant village program. This result becomes a distinctive finding compared to previous evaluation studies in the same location. The importance of youth studies perspective both during the process of planning and evaluating similar development program has to be taken into consideration by the policy maker in order to anticipate the risk of unsustainable development program in the future.Keywords: Youth, generation perspective, development, agropolitant village